DABSO-based, three-component, one-pot sulfone synthesis. - Deeming, A; Russell, C; Hennessy, A; Willis, M (American Chemical Society, 2013)
The addition of Grignard reagents or organolithium reagents to the SO2-surrogate DABSO generates a diverse set of metal sulfinates, suitable for direct conversion to sulfone products. The metal sulfinates can be trapped in situ with a wide range of C-electrophiles, including alkyl, allyl, and benzyl halides, epoxides, and (hetero)aryliodoniums.